2016
DOI: 10.1089/g4h.2016.0038
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Digital e-Health Game for Heart Failure Self-Management: A Feasibility Study

Abstract: Objective: To develop and test the prototype of a serious digital game for improving community-dwelling older adults' heart failure (HF) knowledge and self-management behaviors. The serious game innovatively incorporates evidence-based HF guidelines with contemporary game technology. Materials and Methods: The study included three phases: development of the game prototype, its usability assessment, and evaluation of the game's functionality. Usability testing included researchers' usability assessment, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(124 citation statements)
references
References 30 publications
0
103
0
4
Order By: Relevance
“…Although the search was restricted to articles published in the last 10 years, all eight were published within the last three. Five (63%) were conducted in continental Europe, [24][25][26][27][28] two in United States, 29,30 and one in Jamaica. 31…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the search was restricted to articles published in the last 10 years, all eight were published within the last three. Five (63%) were conducted in continental Europe, [24][25][26][27][28] two in United States, 29,30 and one in Jamaica. 31…”
Section: Resultsmentioning
confidence: 99%
“…Only two of the eight (25%) studies reported a control group. 25,29 Three studies (38%) used a pretest-posttest design, 26,30,31 and three others (38%) evaluated the feasibility of the intervention by collecting adherence outcomes 27,28 or perspectives on the use of the gaming intervention. 24 Six studies did not report any theoretical framework guiding the design of either the study or the game intervention.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interviews solicited information on the impact of HF on quality of life and desired goals for HF self-management. A low-fidelity prototype of the SCDG was developed for the interview using images that presented potential features of a HF digital game, images from a prior HF game, 18 and commercially available sensor devices. A simulation game genre to simulate empathy with a game avatar, which progresses on a mountain and experiences health status changes based on participants' real-time behaviors that are tracked by sensors, was used in the prototype.…”
Section: Data Collectionmentioning
confidence: 99%